The Influence of Fe and Cr Dopant in the Synthesis of Ca3Co4O9 Thermoelectric Material on Crystal Structure, Crystal Size, Thermal Conductivity, and Electrical Conductivity - Imam Syafrudin Rahman; Rachmat Triandi Tjahjanto; Masruroh Masruroh (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2024)
In this work, we study, by sol-gel method, CCO doped with Fe and Cr dopants, the implications for the aspects, crystal structure, crystal size, thermal conductivity, and electrical conductivity. Nevertheless, CCO has low thermoelectric efficiency and thus still longs for optimization in response to the performance, stability, and ecological environment requirement, which needs improvement. Dope would enhance the concentration of charge carriers without modifying the material structure itself. X-ray diffraction (XRD) to characterize the crystal structure and the Williamson–Hall (WH) method to calculate the crystal size were performed. SEM-EDS analyses provide surface morphology, particle size distribution, and elemental composition. The results show that the dopants change, among others, crystal size, microstrain, crystallinity index, and thermal and electrical conductivity, but no change in the crystal structure itself for any of these dopants. Fe doping increased the crystal size of CCO to 144.816 nm (versus 143.382 nm for pure CCO). Compared to Cr doping, the crystal's size was reduced to 65.232 nm. Where the estimated thermal conductivity increased for both dopants, attaining a value of 1.985967 W/mK for CCO-Fe and 1.952233 W/mK for CCO-Cr, concerning the value of 1.740633 W/mK of undoped CCO. Electrical conductivity also expanded (14.50 S/cm for CCO; 14.67 S/cm for CCO-Fe; 14.83 S/cm for CCO-Cr). These improvements highlight the potency of Fe and Cr dopants to fine-tune the CCO for thermoelectric usage.